(untitled) (World of finance, 2019)
Introduction. At the current stage of development of the economy of Ukraine the agro-industry sector acts as a kind of locomotive and determines its volume, supply and value of the main types of food for the population. It greatly affects socio-economic development state, forming 14% of gross value added and more than 40% of exports of countries. Almost 90% of the food needs of the country’s population satisfies for the expense of domestic production. Active development of the world markets for agricultural products requires the formation of an effective one mechanism of financial support of production and investment activity agro-industrial sector of Ukraine taking into account global sustainable goals development. Purpose. The purpose of the article is to find out the features, trends and problems of financial support for the sustainable development of the agro-industrial sector of the economy, substantiation of directions for its improvement Results. The article focuses on the issue of financial security of sustainable development of the agro-industrial sector of the economy, indicators that affect the volume of sales revenue enterprises of the agro-industrial sector. The structure of the sources of financial support of the enterprises of the agro-industrial sector is analyzed and positive and negative tendencies towards its formation are found out. The features of the formation and use of profit as the main source of formation of own capital of enterprises of the agro-industrial sector are analyzed. It is revealed that there is a tendency to decrease the profitability of indicators of enterprises negatively affects the financial security of their sustainable development. Conclusions. It is substantiated that in order to improve the system of financial support for the sustainable development of agro-industrial enterprises the sector needs: – to apply anti-crisis measures, which include the mechanism of the state financial incentives for socially responsible ecologically safe business entities; – to develop a mechanism for state financial incentives production of organic agricultural products; – to develop effective regional strategies for attracting investment resources taking into account the peculiarities of each region’s development; – to develop an effective mechanism for lending agro-industrial the economy sector.